On the Basis of Computer Analysis of the Current Situation of Energy Conservation and Consumption Reduction in China's Iron and Steel Industry and Research Measures. Issue 2 (August 2021) - Bi, Kegang; Yu, Bao; Guo, Baojin; Bi, Yongjiang
Abstract: Adhering to the strategy of energy conservation and emission reduction is one of the important principles of China's industrial development. As one of the indispensable pillar industries of the national economy with high energy consumption and emissions. at the same time because of the restriction of the natural environment conditions, the high-speed development of behind to face the problem of the shortage of resources, ecological destruction, in order to improve people's quality of life and life experience, improve the level of energy conservation and emissions reduction iron and steel industry is imperative. Steel smelting industry, comprehensive considering the steel utilization, energy conservation and emissions reduction targets, etc., have noticed that the costs in smelting system energy-saving, the importance of the question is, society for steel utilization, can't bring enough money for the iron and steel smelting industry benefit, and hindered the development of new energy saving technology, increased the energy saving of iron and steel smelting system pressure. Thus it can be seen that cost capital is the main problem of energy saving in modern iron and steel smelting system. Only with financial support can the level of energy saving be improved.